Hijab, Identitas, dan Religiusitas: Konstruksi Makna dan Praktik Keberagamaan Mahasiswi di Kampus Islam - Agatha Lola Margareta; M Jadid Khadavi (Pustaka Peradaban, 2025)
This study examines the relationship between hijab usage and religiosity among female students at the Institut Ahmad Dahlan (IAD) Probolinggo. It aims to explore the correlation between wearing the hijab and various aspects of religious behavior, including worship practices, understanding of religious values, and social interactions. Employing a qualitative approach with a descriptive phenomenological design, data were collected through in-depth interviews, participant observation, and social media documentation involving students from various academic programs and hijab styles (square hijab, pashmina, and khimar). Informants were purposively selected based on their consistent hijab-wearing behavior, involvement in religious activities, and active presence on social media. The findings indicate that the hijab serves not only as a symbol of Islamic identity but also as an indicator of religiosity. Khimar users, typically from religious family backgrounds and pesantren education, demonstrated greater consistency in religious practices and understanding. In contrast, pashmina and square hijab users tended to be more responsive to social media trends while maintaining modesty. Religious education—particularly within the Islamic Education Department—played a significant role in strengthening religious commitment and influencing the choice of shari'a-compliant hijab styles. Social media also contributed to shaping Islamic identity through da'wah content and Muslim fashion trends. This study concludes that hijab style reflects a complex interaction between social norms, religious values, and individual agency. Islamic identity is dynamically constructed through the internalization of values and the influence of socio-cultural environments. Penelitian ini mengkaji hubungan antara penggunaan hijab dan religiusitas dalam perilaku keberagamaan mahasiswi di Institut Ahmad Dahlan (IAD) Probolinggo. Tujuannya adalah memahami korelasi antara pemakaian hijab dengan praktik ibadah, pemahaman nilai agama, dan interaksi sosial. Menggunakan pendekatan kualitatif fenomenologi deskriptif, data diperoleh melalui wawancara mendalam, observasi partisipatif, dan dokumentasi media sosial terhadap mahasiswi dari berbagai program studi dan gaya hijab (segi empat, pashmina, khimar). Informan dipilih secara purposive berdasarkan konsistensi berhijab, keterlibatan keagamaan, dan aktivitas media sosial. Hasil penelitian menunjukkan bahwa hijab berfungsi sebagai simbol identitas keislaman sekaligus indikator tingkat religiusitas. Pengguna khimar umumnya berasal dari latar keluarga religius dan pendidikan pesantren, menunjukkan konsistensi dalam ibadah dan pemahaman agama. Sementara itu, pengguna pashmina dan segi empat lebih adaptif terhadap tren media sosial namun tetap menjaga kesopanan. Pendidikan agama, khususnya di Prodi PAI, memperkuat komitmen beragama dan pemilihan hijab syar’i, sedangkan media sosial membentuk identitas keislaman melalui konten dakwah dan fesyen Muslimah. Temuan ini menunjukkan bahwa gaya berhijab merupakan hasil interaksi kompleks antara norma sosial, nilai agama, dan agensi individu. Identitas keislaman dibentuk secara dinamis melalui proses internalisasi nilai dan pengaruh lingkungan sosial.